2008
DOI: 10.1016/j.physc.2008.05.268
|View full text |Cite
|
Sign up to set email alerts
|

Rapid change of electronic anisotropy in overdoped (Y, Ca)Ba2Cu3O7−δ

Abstract: Electronic anisotropy was studied for overdoped (Y,Ca)Ba 2 Cu 3 O 7-δ with various doping levels (p). It was found that the pseudogap-like behavior in the resistivity disappear when p exceeds 0.17, independent of the oxygen deficiency. The anisotropy ratio γ estimated from upper critical fields showed a rapid decrease at around p = 0.18, approaching γ = 3 for p > 0.20.1

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 12 publications
3
12
0
Order By: Relevance
“…As we reported in Ref. 24 ␥ rapidly decreases with overdoping and reaches the band calculation value ͑ϳ3͒ at p ϳ 0.18. This is another support for the recovering of three dimensionality observed in the YY spectrum and for the presence of critical doping at p = 0.19 where the pseudogap closes.…”
Section: Discussionsupporting
confidence: 77%
“…As we reported in Ref. 24 ␥ rapidly decreases with overdoping and reaches the band calculation value ͑ϳ3͒ at p ϳ 0.18. This is another support for the recovering of three dimensionality observed in the YY spectrum and for the presence of critical doping at p = 0.19 where the pseudogap closes.…”
Section: Discussionsupporting
confidence: 77%
“…Despite this fact, continuous efforts have been devoted to extracting this basic parameter, through resistive transport, magnetization, and other kinds of experiments. [2][3][4][5][6] Comparing with hole-doped counterparts, anisotropic properties of electron-doped cuprates Ln 2−x Ce x CuO 4−δ (Ln = Nd, Pr, ...) have been less studied and controversial results exist. For instance, an early work in Nd 2−x Ce x CuO 4−δ (NCCO) reported a large γ of 21, 7 while subsequent magnetization measurement in aligned Sm 1.85 Ce 0.15 CuO 4−δ (SCCO) powders gave a low γ of 3.7 and suggested that previous report might be an overestimate due to the inaccuracy in determining the H ab c2 .…”
Section: Introductionmentioning
confidence: 99%
“…Behaviour of the resistivity of our sample in the normal state ( Fig.7 (a)) is typical for optimally doped YBCO [22][23][24]. For T > 93 K, R c (T ) changes in the same way as ρ ab (T ).…”
Section: Discussionmentioning
confidence: 77%